Genomic analysis of SARS‐CoV‐2 in forensic autopsy cases of COVID‐19 - Hirata, Yuichiro; Katano, Harutaka; Iida, Shun; Mine, Sohtaro; Nagasawa, Sayaka; Makino, Yohsuke; Motomura, Ayumi; Ozono, Seiya; Sato, Yuko; Sekizuka, Tsuyoshi; Kuroda, Makoto; Yamaguchi, Rutsuko; et al. (Journal of Medical Virology, 2023)
Numerous genomic analyses of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) have been conducted, highlighting its variations and lineage transitions. Despite the importance of forensic autopsy in investigating deaths due to coronavirus disease 2019 (COVID‐19), including out‐of‐hospital deaths, viral genomic analysis has rarely been reported due in part to postmortem changes. In this study, various specimens were collected from 18 forensic autopsy cases with SARS‐CoV‐2 infection. Reverse‐transcription quantitative polymerase chain reaction revealed the distribution of the virus in the body, primarily in the respiratory organs. Next‐generation sequencing determined the complete genome sequences in 15 of the 18 cases, although some cases showed severe postmortem changes or degradation of tissue RNA. Intrahost genomic diversity of the virus was identified in one case of death due to COVID‐19. The accumulation of single‐nucleotide variations in the lung of the case suggested the intrahost evolution of SARS‐CoV‐2. Lung of the case showed diffuse alveolar damage histologically and positivity for SARS‐CoV‐2 by immunohistochemical analysis and in situ hybridization, indicating virus‐associated pneumonia. This study provides insights into the feasibility of genomic analysis of SARS‐CoV‐2 in forensic autopsy cases and the potential for uncovering important information in COVID‐19 deaths, including out‐of‐hospital deaths.